2020
DOI: 10.1155/2020/8468219
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Treatment with Xiaoqinglong Formula for Bronchial Asthma in Acute Attack: A Systematic Review of Randomized Controlled Trials

Abstract: Background. XQLF (Xiaoqinglong formula) is the most commonly used prescription of traditional Chinese medicine in the treatment of asthma. XQLF combined with western medicine has been used to treat bronchial asthma in more and more cases, and good results have been achieved. Therefore, this meta-analysis aimed to evaluate the adjuvant treatment of traditional Chinese medicine classic herbal formula XQLF with bronchial asthma in acute attack. Methods. The following electronic databases were systematically searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Clinical studies have reported that YPFP appears to have an ameliorative effect on symptoms such as nasal itching and sneezing ( Cheong et al, 2022 ), and reduces the levels of interleukins like IgE and IL-4 in patients with AR ( Fang et al, 2014 ). Xiao-qing-long Tang (XQLT) (from the book Shang-Han-Lun by Zhongjing Zhang , who is regarded a medical genius by later generations), has the effect of warming the lung to dissipate cold, which can effectively treat respiratory diseases ( Wang et al, 2020 ). A systematic review and meta-analysis of randomized controlled trials demonstrated that oral XQLT can relieve AR symptoms and is effective and safe for clinical use ( Yan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported that YPFP appears to have an ameliorative effect on symptoms such as nasal itching and sneezing ( Cheong et al, 2022 ), and reduces the levels of interleukins like IgE and IL-4 in patients with AR ( Fang et al, 2014 ). Xiao-qing-long Tang (XQLT) (from the book Shang-Han-Lun by Zhongjing Zhang , who is regarded a medical genius by later generations), has the effect of warming the lung to dissipate cold, which can effectively treat respiratory diseases ( Wang et al, 2020 ). A systematic review and meta-analysis of randomized controlled trials demonstrated that oral XQLT can relieve AR symptoms and is effective and safe for clinical use ( Yan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a classic Chinese medicine prescription, XQLD has been commonly used in the treatment of allergic diseases such as asthma and AR in clinical practice [6,17]. However, because its therapeutic mechanism has not been fully described, XQLD still lacks a sufficient theoretical basis for its further clinical promotion and application.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 inflammatory response and destruction of nasal epithelial function are key pathological changes in AR progression [18,19]. Previous studies have reported the therapeutic effect of XQLD on immune response [17], but the regulation mechanism still needs more ascertained proof. In our study, XQLD has been demonstrated to directly inhibit the expression of type 2 inflammatory cytokines (IL4, IL5, and IL13).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the effect of traditional Chinese medicine in treating AR has been gradually recognized [13], and the research on mechanism of TCM to treat AR has attracted a lot of attention. As a classic Chinese medicine prescription, XQLD has been commonly used in the treatment of allergic diseases such as asthma and AR in clinical practice [11,14].…”
Section: Discussionmentioning
confidence: 99%